2020
DOI: 10.1021/acsami.9b20924
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Adsorbents with Enhanced Hydrophobicity for Oil Spill Removal

Abstract: Oil spills cause massive loss of aquatic life. Oil spill cleanup can be very expensive, have secondary environmental impacts, or be difficult to implement. This study employed five different adsorbents: (1) commercially available byproduct Douglas fir biochar (BC) (SA ∼ 695 m 2 /g, pore volume ∼ 0.26 cm 3 /g, and pore diameter ∼ 13−19.5 Å); (2) BC modified with lauric acid (LBC); (3) iron oxide-modified biochar (MBC); (4) LBC modified with iron oxide (LMBC); and (5) MBC modified with lauric acid (MLBC) for oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Navarathna et al, also reported the product of lauric acid decorated magnetic biochar (MLBC) as a dispersible oil sorbent (Figure 13E). [33] MLBC can fully recycle into fuel, similar to calorimetry with oil fuels. Kang et al, fabricated magnetic carbon nanosphere/nitrogen doped graphene aerogel with a one-step hydrothermal in situ electrostatic selfassembling method under weakly alkaline (Figure 13F).…”
Section: Strategies For Sorbent Collection With Magnetic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Navarathna et al, also reported the product of lauric acid decorated magnetic biochar (MLBC) as a dispersible oil sorbent (Figure 13E). [33] MLBC can fully recycle into fuel, similar to calorimetry with oil fuels. Kang et al, fabricated magnetic carbon nanosphere/nitrogen doped graphene aerogel with a one-step hydrothermal in situ electrostatic selfassembling method under weakly alkaline (Figure 13F).…”
Section: Strategies For Sorbent Collection With Magnetic Responsementioning
confidence: 99%
“…[28][29][30][31] Several studies have reported that sorbents with high-performance can easily be obtained by precise tuning of a sorbent's hydrophobicity and swelling capacity. [32,33] Modified sorbents with diverse morphologies, [34][35][36] wettability, [37][38][39][40][41] and specific surface area functions have generated to exploit high oil sorption capacity and reusability, [42][43][44][45][46][47] and these modified sorbents are now playing an important role in oil spill remediation. For example, heating sorbents allow absorption of highly viscous oil efficiently.…”
mentioning
confidence: 99%
“…Sorption is probably one of the most used methods because oil sorbents fall into two very broad categories: synthetic, such as polyanilines and polypyrrole-silica polymer composites [ 21 , 22 ], and natural adsorbents, such as bio-based aerogels and natural adsorbents based on sawdust [ 23 , 24 ]. The latter can be further divided into organic and inorganic [ 25 , 26 ]. Synthesis of composite materials employing both synthetic and natural substances is a developing technique and the amount of published research is fast growing [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar (BC) is a pyrogenic carbon (C)‐rich material with good biocompatibility, high specific surface area, and abundant pore structures and functional groups, and it can serve as a promising adsorbent, 19 carrier 20,21 and soil amendment 22 . Outstanding physicochemical properties confer a high loading capacity on BC, yet BC modification has gained massive recent interest, as specific modifications can enhance these properties, providing larger specific surface area, greater pore volume, higher negative zeta potential, more oxygen (O)‐containing functional groups, and stronger pollutant adsorption capacity 23,24 .…”
Section: Introductionmentioning
confidence: 99%